Direct algorithm for the solution of two-sided obstacle problems with M-matrix - Jiang, Ying-Jun; Zeng, Jin-Ping (Numerical linear algebra with applications, 2011)
A direct algorithm for the solution to the affine two‐sided obstacle problem with an M‐matrix is presented. The algorithm has the polynomial bounded computational complexity O(n3) and is more efficient than those in (Numer. Linear Algebra Appl. 2006; 13:543–551). Copyright © 2010 John Wiley & Sons, Ltd.